Chapter Manipulation of Photonic Orbital Angular Momentum for Quantum Information Processing - Nagali, Eleonora; Sciarrino, Fabio (InTechOpen, 2012)
Computer modelling & simulation
English
Keywords: Computer modelling & simulation; Computing & information technology